Forced Migrants in Serbia: Refugees and Internally Displaced Persons - Facts and Figures, Coping Strategies, Future - Bobic, Mirjana (Refuge: Canada’s Journal on Refugees, 2010)
<!–StartFragment–> The paper deals with refugees and internally displaced persons (IDPs). Considering their numbers, Serbia is the first in Europe and fourteenth on the globe. Their destiny is not only a tragic epilogue to the political dissolution of the former Yugoslavia, but also to the breakdown of the common dream of “Yugoslav” nationality (which was meant to be a “melting pot” of various nations, ethnic groups, and religions). Unfortunately, due to the specific strategy of nation-state building based on ethnic cleansing, refugees were one of the direct objectives of civil wars taking place in the 1990s. At the same time, massive floods of IDPs were instigated by the bombing campaign of Kosovo and Metohija conducted by the NATO alliance in 1999. Having come to Serbia, the majority of both refugees and IDPs who are ethnic Serbs have attained all the features of minority groups. The reasons for their social exclusion must be discussed in terms of their exceptionally low social position, high levels of unemployment and poverty, and lack of social inclusion. Moreover, it must be taken into account that contemporary Serbia faced many unresolved political challenges, delayed accession to the EU, secession of Kosovo and Metohija in 2008, hardships in establishing a market economy and liberal democracy since 2000, and economic deprivation, all of which were accompanied by poor social services. Serbian authorities adopted four major action plans targeted at forced migrants. However, the main challenges to their applicability stem from lack of institutional capacities, ineffective implementation of development strategies, and limited resources. <!–EndFragment–>